(untitled) (Journal of the College of Basic Education, 2022)
The current research objective defines the training needs of kindergarten teachers from their point of view .And verification of the significance of statistical differences in the estimates of the parameters of the training needs for them in kindergartens according to the variables of the educational qualification (Institute Parameters) (Preparatory) (Department of kindergartens College of Education or Basic Education) (Certificate of Graduate kindergartens) (Other Specialties) And the years of service and interaction between them. The current research was adopted descriptive approach to determine the training needs of kindergarten teachers. The sample consisted of (250) teachers from Baghdad governorate, the general directorates of Rasafa education (1,2,3) For kindergarten teachers from their point of view, they consist of six fields and (38) paragraphs. The five-dimensional scale was adopted and the research reached the following results In terms of the results of the first target, the descending order of the training needs areas of the kindergarten teachers ranked first in the field of the tool. The field of professional and educational knowledge ranked second, the third ranked field, the fourth rank field, the field of education methods, Educational ranked sixth in the sequence of fields And the requirements were ranked in descending order. The mean averages ranged between (1.64) and (4.66), a difference (3,02) between the highest and lowest mathematical averages. The descending order of the training needs of 79% is the subject of training needs, Children and 21% represent a few needs of teachers. There are statistically significant differences between the arithmetical averages of the estimates of the sample members on the instrument due to the variable (scientific qualification) There were no statistically significant differences between the arithmetical averages of the estimates of the sample members on the instrument due to the interaction variable between the academic qualification and the years of service.